If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(p + -1) = 2p + -5 Reorder the terms: 5(-1 + p) = 2p + -5 (-1 * 5 + p * 5) = 2p + -5 (-5 + 5p) = 2p + -5 Reorder the terms: -5 + 5p = -5 + 2p Add '5' to each side of the equation. -5 + 5 + 5p = -5 + 5 + 2p Combine like terms: -5 + 5 = 0 0 + 5p = -5 + 5 + 2p 5p = -5 + 5 + 2p Combine like terms: -5 + 5 = 0 5p = 0 + 2p 5p = 2p Solving 5p = 2p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-2p' to each side of the equation. 5p + -2p = 2p + -2p Combine like terms: 5p + -2p = 3p 3p = 2p + -2p Combine like terms: 2p + -2p = 0 3p = 0 Divide each side by '3'. p = 0 Simplifying p = 0
| W=(a+R) | | n^2+13n+36= | | 2x-4(-3x+4)=68 | | 28x^3-7x^2+8x-2=0 | | 6x(x)=864 | | -5+8p=-25 | | 30u^2-57u+21= | | x^2+23x+130= | | 2x-7(x+10)=-45 | | (y-1)/3=2 | | 14x^2+2x-12= | | 2x^2(x^4+3x^2-5)= | | (3x^2+4x-7)(8-2x+x^2)= | | 3x-14=-16 | | (13v^2+5v^4)-(2v^5-v^4-v^2)= | | .5x^2=12x | | -16=14-3x | | X^2+13x+33=0 | | 2n=5n+12 | | 2-6x-8x+7= | | x^2y+8y+9x^2+72= | | 36/72 | | -4(5c-6)+4n= | | 15w+50=-1 | | 9x^2+6x-80= | | factorz^5+4z^3-2z^2-8=0 | | 3x=10-7x | | 24+11t+t^2=0 | | 3cos(3x)-1=0 | | 6x^2-60x= | | 7.5w+25=-1 | | 2x+12+3x-18+3z+4y=360 |